Cultura de segurança em aeroportos: proposta de metodologia para avaliação quantitativa - Gomes, Wilson Rocha (2018)
The present research had as objective to propose a metric that represents the degree of the safety culture in operational activities in the airports, according to the adapted model of Cooper (2000). The justification for this study was due to the latent imbalance between production and safety in the air transport modality, since accidents continue to recur at Brazilian airports over time, and from the perspective that a positive safety culture can act as an antecedent for the prevention of accidents. This model included two units of analysis: the individual (components Psychological Factors and Behavior of Security) and the organization (Security Management System). In this exploratory study, a questionnaire containing 47 questions for the collection of Psychological Factors data was used, a checklist containing 44 standard behaviors for the data collection of the Safety Behavior factor, and access to Primary Sources for the collection of data. data related to the Operational Safety Management System - SGSO. The research was applied at the international airport Afonso Pena, administered by Infraero, located in the city of São José dos Pinhais, Paraná, Brazil. The result of the application of the theoretical model was denominated NACSO - Acceptable level of operational safety, reaching the value of 4.45 points. It is recommended, for a better development of the operational safety culture, that the results of the NACSO qualitative analyzes be submitted to the Risk Management process of an SGSO.